Modeling harmonically modelocked fiber lasers - Horowitz, Moshe; Menyuk, Curtis (Optica, 1999)
Modelocked erbium-doped fiber lasers which are used for communication should work with high repetition rate.
Conference on Lasers and Electro-Optics 1999, Baltimore, Maryland United States, 23–26 May 1999
Keywords: Laser systems; Pulse shaping; Erbium fibers; UMBC Optical Fiber Communications Laboratory; UMBC High Performance Computing Facility (HPCF); Nonlinear effects; Lasers; Fiber lasers